Differential efficacy of two psychosocial therapies in the treatment of psychopathology associated with epilepsy among selected patients at federal medical centre, Owo, Nigeria - Bayo L. AJIBADE; Patience O. AMOO; Zacheus O. OYEWUMI; Wale AKINPELU; Raphael A. AYENI (International Journal of Medical Research and Review, 2015)
Introduction:Epilepsy is a common medical and social disorder or group of disorders with unique characteristics. It has been postulated that there is a relationship between behavioural, physiological and psychological states and probability of seizure occurrence. Therefore, this study examined the efficacy of Rational Emotive Therapy and cognitive restructuring on the reduction of psychopathology associated with Epilepsy.Methodology: A 3 x 2 factorial experimental design was adopted in testing two (2) null hypotheses. Ninety (90) Epileptic patients were randomly selected and administered with the therapeutic packages for a period of 7weeks. The respondents were divided into 2 experimental and one control groups. Washington Psychosocial seizure inventory (WPSI) was the only instrument used.Result:Results indicated that subjects exposed to treatment performed significantly better than control group on the reduction of Psychopathology associated with Epilepsy. The two treatment strategies were equally effective in fostering the reduction of Psychopathology associated with epilepsy. Female subjects in the two treatment condition excelled better than their male counterparts on the reduction of psychopathology of Epilepsy.Conclusion: It was concluded that mental health/psychiatrics nurses should always remember to accompany the use of drugs with psychotherapy so that the patient will be aware of psychopathology associated with the illness. This will prevent them from developing serious psychopathology.